GENERASI MILLENIAL ROKAN HULU TERHADAP KESENIAN TRADISI DAN BUDAYA PADA MASYARAKAT SUKU BONAI RIAU - Syefriani, Syefriani (SENDRATASIK UNP, 2019)
AbstractMillenial generation, is a generation who born and live in current development and advanced technology. It makes them one step beyond from previous generation. However, millennial generation is to busy with their world, so that their so care less with their social environment, or surroundings. Especially at Rokan Hulu, where there are rural communities, named Bonai Tribe. Bonai tribe has so many traditional arts and culture which is required to be known and studied by millennial generation. Which aims to maintain and preserve, so that existing arts and culture can be maintained.Â Keywords : Millenial Generations, Bonai Tribe, Traditional Arts